RATIONAL ANTIBIOTIC THERAPY IN THE TREATMENT OF INFLAMMATORY PERIODONTAL DISEASES: RESULTS OF LONG-TERM CLINICAL AND LABORATORY EXPERIENCE - Kostenko, Yеvhen; Kryvtsova, Maryna; Skliar, Ivan; Kostenko, Oleksandr; Dzhupa, Peter; Miglas, Volodimir; Yurzhenko, Anastasiia (Eastern Ukrainian Medical Journal, 2025)
Introduction. The implementation of the principles of rational antibiotic therapy is an important aspect of modern dentistry, which will significantly improve the quality of medical care and contribute to the fight against the problem of antibiotic resistance. Standardization of the test techniques and clear interpretation of the results allow to ensure effective and safe treatment of diseases of the oral cavity of microbial etiology. The aim of the study is to develop recommendations for the implementation of the principles of rational antibiotic therapy in periodontology based on comprehensive assessment of the dominant microbial associations of the oral cavity and their sensitivity to antibiotics. Materials and methods. The study was conducted in 2017–2024 at the Faculty of Dentistry, Uzhhorod National University. The biological material was collected from the locus of the inflammatory process (periodontal pockets) of 525 patients with chronic periodontitis in the acute stage, aged 35–65 years. Differential diagnostic nutrient media were used for the cultivation of opportunistic microbiota. For the cultivation of anaerobic microbiota, Schedler's agar + 5% sheep blood nutrient medium (Himedia, India) was used. To create anaerobic conditions, an anaerobic jar making anaerobic conditions (AnaeroGen System – Oxoid, UK) was used. The antibiotic susceptibility of the bacteria and microscopic fungi was determined by the disc diffusion method according to the recommendations of the European Committee on Antimicrobial Susceptibility Testing (EUCAST). Results. The persistence of polymicrobial (2–5 species) dominant associations related to periodontopathogenic and opportunistic microorganisms in clinically significant titres from 105 to 1010 CFU/ml was established in patients with periodontitis. A high therapeutic effect of antibiotic use was shown on the basis of determining the sensitivity of association microorganisms to antibiotics. The EUCAST principles were applied in the analysis of the antibiograms. Conclusions. Based on many years of clinical and laboratory experience, a comprehensive algorithm for microbiological screening of the oral cavity in inflammatory periodontal diseases has been developed. The persistence of periodontopathogenic and opportunistic microorganisms consisting of 2–5 associates in titres of 105–1010 CFU/ml was established under conditions of periodontitis. It has been shown that determination of antimicrobial susceptibility of the entire microbial association leads to effective elimination or clear reduction of clinically significant titres of microorganisms. A comparison of antibioticograms of periodontopathogenic and opportunistic microorganisms provides the maximum therapeutic effect.